PMP(Porphyrin-Micelle-PSMA) Nanoparticles for Photoacoustic and Ultrasound Signal Amplification in Mouse Prostate Cancer Xenografts - Daehyun Kim; Wonkook Han; Jin Ho Chang; Hak Jong Lee (MDPI AG, 2021)
Photoacoustic (PA) imaging is used widely in cancer diagnosis. However, the availability of PA agents has not made great progress due to the limitations of the one currently in use, porphyrin. Porphyrin-Micelle (PM), developed by synthesizing porphyrin and PEG-3.5k, confirmed the amplification of the PA agent signal, and added binding affinity in an LNCaP model by attaching prostate-specific membrane antigen PSMA. Compared to the previously used porphyrin, a superior signal was confirmed, and the potential of PMP was confirmed when it showed a signal superior to that of hemoglobin at the same concentration. In addition, in the in vivo mouse experiment, it was confirmed that the signal in the LNCaP xenograft model was stronger than that in the PC-3 xenograft model, and the PMP signal was about three times higher than that of PM and porphyrin.